Вера, Надежда, Любовь...: женские портреты / Безелянский Ю.Н. - Безелянский Юрий Николаевич (Радуга, 1999)
Экземпляры: СЭ (20000808) / Инвентарный номер: 1036216 / Цена: 36.00 / Сис.шифр: 63.3(2)5 / Авт.знак: Б 39 / ГРНТИ: 03 / ББК: 63.3(2)52